The Impact of Artificial Intelligence on High School Students’ Writing Anxiety in Continuation Writing - Zhang, Meidong (Scientific Journal of Technology, 2026)
Artificial intelligence is reshaping English writing instruction, offering new possibilities for alleviating senior high school students’ anxiety in continuation writing tasks. Grounded in control-value and sociocultural theories, this study positions AI as a "cognitive partner." Through in-depth interviews with 12 students, the research reveals that AI mitigates anxiety by enhancing perceived control via three pathways: cognitive load sharing, immediate feedback regulation, and positive emotion activation. However, AI use may also trigger new forms of anxiety, including dependence, evaluation, and value anxiety. Students expect clear rules, personalized support, and autonomy preservation. Accordingly, the study proposes four pedagogical pathways for human-AI collaboration: teacher role transformation, boundary setting, differentiated intervention, and value clarification. It emphasizes that AI is not a substitute for teachers but a cognitive partner, and that the key to alleviating anxiety lies not in the technology itself, but in the mode of human-technology collaboration.